Psychological health in preschool children with underweight, overweight or obesity: a regional cohort study - Geir Egil Eide; Trond Markestad; Petur Juliusson; Hilde Mjell Donkor; Helene Toxe; Jørgen Hurum; Robert Bjerknes (BMJ Publishing Group, 2021)
Objective To examine if underweight (UW), overweight (OW) or obesity (OB), or body mass index (BMI) expressed as its SD score (BMI SDS), were associated with psychological difficulties in preschool children.Design Regional cohort study.Setting Oppland County, Norway.Methods At the routine school entry health assessment at 5-6 years of age, parents were invited to participate by local public health nurses. The parents completed questionnaires on sociodemographic, health and lifestyle factors of the child and the family, and on the child's neurocognitive development. They assessed psychological health with the Strengths and Difficulties Questionnaire (SDQ). Public health nurses measured weight and height on all eligible children and reported age, sex, height and weight anonymously for the children who declined to participate.Participants We obtained information on 1088 of 1895 (57%) eligible children. The proportion of UW, OW and OB was slightly higher among the children who declined.Main outcome measures SDQ subscale and Total Difficulties Scores.Results The mean SDQ scores and proportion of scores ≥the 90th percentile had a curvilinear pattern from UW through normal weight (NW), OW and OB with NW as nadir, but the pattern was only significant for the mean Emotional problems, Peer problems and Total SDQ Scales, and for the Total SDQ Score ≥the 90th percentile (TDS90). After adjusting for relevant social, developmental, health and behavioural characteristics, TDS90 was only significantly associated with UW in multiple logistic regression analyses, and only with the lowest quartile of BMI SDS in a linear spline regression analysis.Conclusions The study suggests that UW and low BMI, but not OW, OB or higher BMI, are independent risk factors for having psychological symptoms in preschool children.